Dampak Experiential Marketing dan E-WOM terhadap Minat Pembelian Ulang di Eightyone Coffee Eatery Kota Medan - Laila Elfiridawaty Situmorang; Rangga Restu Prayogo (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the influence of experiential marketing and electronic word of mouth (E-WOM) on consumer repurchase intentions at Eightyone Coffee Eatery in Medan City. The background of this study is based on the high competition in the coffee shop business and the need for experiential marketing strategies and the use of digital reviews to maintain customer loyalty. This study uses a quantitative method with a descriptive approach. The research sample of 96 respondents was selected using incidental sampling technique, namely Eightyone Coffee Eatery customers who have visited at least twice. Data were collected through a questionnaire and analyzed using multiple linear regression with validity, reliability, t-test (partial), F-test (simultaneous), and coefficient of determination (R²) tests. The results show that experiential marketing has a positive and significant effect on repurchase intentions. Similarly, E-WOM has a positive and significant effect on repurchase intentions. Simultaneously, both variables have a positive and significant effect on repurchase intentions of Eightyone Coffee Eatery consumers. These findings confirm that creating a pleasant consumer experience through sensory, emotional, cognitive, and social aspects, as well as good digital review management, are important factors in encouraging customers to make repeat purchases.